2010
DOI: 10.1111/j.1464-410x.2009.08965.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in small intestinal submucosa evoke differences in inflammation with subsequent impact on tissue regeneration in the rat bladder augmentation model

Abstract: OBJECTIVE To examine the histological differences in the inflammatory response and regenerative outcomes of distal vs proximal porcine small intestinal submucosa (SIS) grafts in the rat bladder, as SIS from distal small intestine yields reliable and reproducible bladder regeneration, while SIS from proximal portions of small intestine does not provide similar results. MATERIALS AND METHODS In all, 30 Sprague‐Dawley rats underwent hemi‐cystectomy followed by anastomosis of a bladder patch of SIS prepared from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
(33 reference statements)
2
35
0
Order By: Relevance
“…On this basis, we confirmed the angiogenic potential of the membrane and demonstrated that the process is temporary, accompanying the reduction of the inflammatory process, important events for the lack of perpetuation of inadequate tissue response to the graft used. An explanation for this phenomenon could be the intense macrophage activity during the early phases of scarring (9), supporting the statement that these cells play a controlling role in fibroblast proliferation and migration, in matrix formation, and in angiogenesis (21,22).…”
Section: Discussionsupporting
confidence: 57%
“…On this basis, we confirmed the angiogenic potential of the membrane and demonstrated that the process is temporary, accompanying the reduction of the inflammatory process, important events for the lack of perpetuation of inadequate tissue response to the graft used. An explanation for this phenomenon could be the intense macrophage activity during the early phases of scarring (9), supporting the statement that these cells play a controlling role in fibroblast proliferation and migration, in matrix formation, and in angiogenesis (21,22).…”
Section: Discussionsupporting
confidence: 57%
“…However, in two separate studies by Ashley et al, unseeded SIS would be found to be highly pro-inflammatory. (Ashley, 2009(Ashley, , 2010 The seminal work that laid the foundation for future bladder regenerative studies came from Oberpenning et al Within this study, autologous sources of canine urothelial and smooth muscle cells were harvested then seeded onto polymers and subsequently expanded ex vivo. Completely cystectomized canines were then transplanted with this new bladder construct and observed for approximately a year.…”
Section: The Urinary Bladdermentioning
confidence: 99%
“…However, in two separate studies by Ashley et al, unseeded SIS would be found to be highly pro-inflammatory. (Ashley, 2009(Ashley, , 2010 The seminal work that laid the foundation for future bladder regenerative studies came from Oberpenning et al (Oberpenning, 1999) Within this study, autologous sources of canine urothelial and smooth muscle cells were harvested then seeded onto polymers and subsequently expanded ex vivo. Completely cystectomized canines were then transplanted with this new bladder construct and observed for approximately a year.…”
Section: The Urinary Bladdermentioning
confidence: 99%